2008
DOI: 10.1080/00103620802292293
|View full text |Cite
|
Sign up to set email alerts
|

Response of Cotton to Irrigation Methods and Nitrogen Fertilization: Yield Components, Water‐Use Efficiency, Nitrogen Uptake, and Recovery

Abstract: Efficient crop use of nitrogen (N) fertilizer is critical from economic and environmental viewpoints, especially under irrigated conditions. Cotton yield parameters, fiber quality, water-and N-use efficiency responses to N, and irrigation methods in northern Syria were evaluated. Field trials were conducted for two growing seasons on a Chromoxerertic Rhodoxeralf. Treatments consisted of drip fertigation, furrow irrigation, and five different rates of N fertilizer (50, 100, 150, 200, and 250 kg N /ha). Cotton w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…In northern Syria, flood-irrigated cotton that yielded 1,800 kg lint/ha, took up 300 kg N/ha, resulting in an iNUE of 6.0 (Janat 2008). There was no increase in lint yield by applying N fertiliser, confirming that these crops took up more N than was required to produce moderate yields and were probably over-supplied with N. Further, apparent N fertiliser recovery was also low (37 and 16% in 2 years), confirming the soil was highly N-fertile (high mineral N content was measured throughout the soil profile).…”
Section: Crop Inue Measurementsmentioning
confidence: 99%
“…In northern Syria, flood-irrigated cotton that yielded 1,800 kg lint/ha, took up 300 kg N/ha, resulting in an iNUE of 6.0 (Janat 2008). There was no increase in lint yield by applying N fertiliser, confirming that these crops took up more N than was required to produce moderate yields and were probably over-supplied with N. Further, apparent N fertiliser recovery was also low (37 and 16% in 2 years), confirming the soil was highly N-fertile (high mineral N content was measured throughout the soil profile).…”
Section: Crop Inue Measurementsmentioning
confidence: 99%
“…The cultivation of cotton with its high N requirements (50-412 kg N ha −1 ) and the need for irrigation water (177-463 mm yr −1 , Aneja et al 1996;Navarro et al 1997;Hou et al 2007;Mahmood et al 2008;Janat 2008;Scheer et al 2008a, b;Zhang et al 2008) creates potentially favorable conditions for especially denitrifying microbial activity in the agricultural soil that can result in high emissions of N 2 O and NO. Indeed, significant emissions of these N gases have been observed from cotton fields across the globe (Aneja et al 1996;Mahmood et al 2008;Scheer et al 2008a, b) and the N recoveries from the crop are usually low (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have demonstrated the appropriateness of using drip irrigation for cotton in water stressed regions (e.g., Bucks, Allen, Roth, & Gardener, 1988;Da gdelen, Bas ‚ al, Yılmaz, Gü rbü z, & Akcay, 2009;DeTar, 2008;Karam et al, 2006;Wang et al, 2012). Several studies have been carried out in the region, which have shown a high potential for water saving and yield increase, particularly when adequate fertilisation is adopted (Farahani, Oweis, & Izzi, 2008Hussein, Janat, & Yakoub, 2011;Janat, 2008;Oweis et al, 2011). However, studies show contradictory results in terms of deficit irrigation (DI), with some clearly considering DI less favourably (e.g., Akhtar, Tischbein, & Awan, 2013;Da gdelen et al, 2009;DeTar, 2008;Ü nlü , Kanber, Koc, Tekin, & Kapur, 2011) and few reporting positive results of DI (e.g., Hussein et al, 2011).…”
Section: Introductionmentioning
confidence: 99%